Domestic Politics and Cross-Strait Relations: A Synthetic Perspective. (March 2020) - Wu, Yu-Shan; Chen, Kuan-Wu
This study examines the association between political competition (elections in Taiwan and political successions in China) and cross-Strait conflicts. We find that the Taiwan president has been more assertive toward mainland China during the election period or in his second term, than during the inter-electoral period or in the first term. The general secretary of the Chinese Communist Party (CCP) reacts to Taiwan's provocations more harshly when he was in a period of power transition than when he had consolidated power. The two phenomena rest on the same assumption: when a political leader is domestically challenged, he cannot appear weak in external behaviors; when the leader is secure in his position, he can afford to make external concessions. We test the assumption against the empirical evidence from the cross-Strait relations of 1989–2012 and find the most serious conflicts occurred during Taiwan's electoral period and when the CCP general secretary was in power transition. The study advances our understanding of how conflicts occur in cross-Strait relations and may lead to possible ways of their prevention.